2008
DOI: 10.1080/00498250701813222
|View full text |Cite
|
Sign up to set email alerts
|

In vitrometabolism of KBH-A40, a novelδ-lactam-based histone deacetylase (HDAC) inhibitor, in human liver microsomes and serum

Abstract: 1. The metabolism of KBH-A40, a novel -lactam-based histone deacetylase (HDAC) inhibitor, was investigated in vitro using human liver microsomes and serum. After 60-min incubation in human liver microsomes with -nicotinamide adenine dinucleotide phosphate (NADPH) or uridine diphosphate glucuronic acid (UDPGA), the residual KBH-A40 was 90.6% AE 5.1% and 28.9% AE 2.0% (t 1/2 ¼ 26 min), respectively, suggesting that KBH-A40 is likely predominantly metabolized by glucuronidation, rather than by cytochrome P450 (CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Taken together, these findings suggest that the rapid hydrolysis in the plasma, exerting an extensive first-pass effect, could be a major reason for the poor oral absorption of KBH-A40. It has been reported by the present authors that KBH-A40 was degraded rapidly in the presence of UDPGA by human liver microsomes and its glucuronide conjugate was identified by using liquid chromatography hybrid quadrupole time-of-flight mass spectrometry analysis (Kim et al, 2008). In this study, our results showed that KBH-A40 was degraded rapidly in the presence of UDPGA by rat liver microsomes.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…Taken together, these findings suggest that the rapid hydrolysis in the plasma, exerting an extensive first-pass effect, could be a major reason for the poor oral absorption of KBH-A40. It has been reported by the present authors that KBH-A40 was degraded rapidly in the presence of UDPGA by human liver microsomes and its glucuronide conjugate was identified by using liquid chromatography hybrid quadrupole time-of-flight mass spectrometry analysis (Kim et al, 2008). In this study, our results showed that KBH-A40 was degraded rapidly in the presence of UDPGA by rat liver microsomes.…”
Section: Discussionsupporting
confidence: 47%
“…Despite this property, the oral bioavailability of KBH-A40 was found to be low (14.2%-14.8%). In our previous study (Kim et al, 2008), KBH-A40 was shown to be rapidly metabolized by hydrolysis to its carboxylate in rat serum. Consistent with this in vitro result, the current pharmacokinetics study demonstrates that KBH-A40 is hydrolyzed rapidly in vivo to its carboxylate after i.v.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic stability is considered an important property of NCEs and is usually quantified by monitoring the disappearance of the parent compound over time in an in vitro system to determine the metabolic half-life (t 1/2 ) and intrinsic clearance (CL int ) [3,4]. Results obtained from in vitro metabolic stability experiments are used to estimate and predict clearance (CL) in vivo at the early stages of drug discovery.…”
Section: Introductionmentioning
confidence: 99%